PENDEKATAN SOSIOLOGI DAN ANTROPOLOGI TENTANG MAHAR - Fitriyani; Hidayat, Deden; Inayatullah, Deden (Fakultas Agama Islam, Universitas Mathla'ul Anwar, 2022)
Mahar is part of Islamic teachings which is an integral part of a marriage. The dowry is set in the spirit of providing protection and placing women in a noble rank. One way to glorify and respect women in Islam is to give her a marriage dowry, the amount and/or amount of which is determined by agreement between the man and woman. This gift is a symbol of respect for the position of women. This paper is a qualitative writing with a descriptive approach, which aims to re-describe dowry using sociological and anthropological approaches. From literacy on marriage fiqh, it is known that there are still differences of opinion regarding dowry, especially with regard to the amount and amount. In this regard, a social approach is needed in the community to be able to provide minimum and maximum limits on the marriage dowry.